Vegetation structure define mite assemblage on plants: a case study in Cerrado biome - Moraes, Vinicius de S.; Nunes, Samuel N.; Demite, Peterson R.; Daud, Rodrigo D. (Entomological Communications, 2022)
We compared abundance and richness of mites on Miconia albicans (Sw.) Steud. (Melastomataceae) found in Cerrado grassland (CGR) and in Cerrado sensu stricto (CSS), in order to evaluate the effect of plant physiognomy on mite assemblage structure, in the Parque Nacional das Emas, Goiás State, Brazil, a biological reserve of Cerrado biome. In total, 453 mites of 45 species belonging to 14 families were collected. Stigmaeidae was the most abundant predatory mite family, represented by a single unidentified Agistemus species. Among phytophagous mites, species of Lorryia (Tydeidae) were the most common. Lorryia turrialbensis Baker, 1968 is reported for the first time on a Cerrado plant species. We concluded that the Cerrado phytophysiognomy can determine the organization of mite assemblages since CSS sheltered higher species richness and abundance of mites on M. albicans due to has more habitat complexity, species richness and abundance of plants than CGR. Therefore, CSS can provide more food resources, microhabitats for shelter and oviposition favoring the occurrence and populational development of plant mites.